Pengaruh Pemikiran Nashiruddin Al-Thusi terhadap Perkembangan Metode Penentuan Arah Kiblat - Jannah, Elly Uzlifatul; Sulthon , Mohammad (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
This research aims to analyze the influence of Nashiruddin al-Thusi's thoughts on developing methods for determining Qibla direction using the library research method. The research results stated that Nashiruddin al-Thusi was a leading astronomer of his time, and his work covered various aspects of astronomy, including determining the direction of the Qibla. His thoughts regarding astronomy were based on a scientific approach and accurate observations of celestial phenomena. He combined the principles of geometry, mathematics and natural philosophy. Al-Thusi's thoughts regarding astronomy significantly contributed to the understanding and development of astronomical science in his time. He consolidated the thinking of his predecessor scientists and made significant contributions to advancing astronomical thinking. Furthermore, the influence of al-Thusi's thoughts on the development of the Qibla direction method was revolutionary. Al-Thusi proposed an incredibly innovative method for determining the direction of the Qibla by referencing the declination or annual position of the sun, a concept that continues to be the foundation for modern methods of determining the Qibla direction. His innovative approach not only revolutionized the field of astronomy but also had a significant impact on the development of modern astronomical instruments.